O MAL NA LITERATURA MACHADIANA: UMA LEITURA TEOLÓGICA E FILOSÓFICA DA OBRA QUINCAS BORBA, DE MACHADO DE ASSIS - Fuchigami, Ivna Maia (2014)
The present research conducts a study about evil based on the book Quincas Borba, by Machado de Assis, under the theological and philosophical viewpoint as the subject has raised several questions in both fields of knowledge. At one time, we intend to indicate that it is possible that a literary work may inspire a theological and philosophical thought without being necessary to prove the religious faith or to unveil a philosophical theory established by the writer. For that purpose, we suggest as authors the theologians Andrés Torres Queiruga, Juan Antonio Estrada, and Ivone Gebara, as well as the philosophers Paul Ric ur, Blaise Pascal and Arthur Schopenhauer. At the same time, we emphasize the Book of Ecclesiastes, of which the carioca writer was a constant reader. Therefore we aim at highlighting and understanding more deeply in the above mentioned book the presence of evil in its most varied aspects in human relations.